Mutual funds and other institutional investors; a new perspective - Friend, Irwin; Blume, Marshall; Crockett, Jean; Twentieth Century Fund. (New York, McGraw-Hill, 1970)
The study analyzes the implications for the economy as a whole of the increasing importance of institutional investors in the stock market, with particular emphasis o mutual funds. Mutual funds and pension funds carried out the bulk of the new institutional stock investment in recent years and together with personal trust funds administered by commercial banks, accounted for most institutional stockholdings.
"A Twentieth Century Fund study."
Includes bibliographical references.
usc 18/5/17
Loans
Keywords: Mutual funds